Mild hypothermia protects rat neuronal injury after intracerebral hemorrhage via attenuating endoplasmic reticulum response induced neuron apoptosis. (2nd December 2016) - Guo, Cen; Geng, Yang; Song, Feifei; Huo, Yajing; Wu, Xuqing; Lv, Jianing; Ge, Anyan; Fan, Wei
Highlights: ICH injury induces endoplasmic reticulum (ER) stress response. Mild hypothermia could attenuate intracerebral hemorrhage (ICH) caused neuron injury by decreasing neuron apoptosis. Mild hypothermia decreased ER response after ICH. Abstract: Background and purpose: Mild hypothermia has been proved to reduce global and focal cerebral ischemic injury in rodents by preventing cellular apoptosis through several pathways. However, whether hypothermia will be beneficial for intracerebral hemorrhage (ICH) and its underlying mechanisms haven't reached a consensus. It has been implicated that endoplasmic reticulum (ER) stress plays a role in the secondary injury after ICH in rats. In this study, we aimed to investigate whether mild hypothermia would attenuate ICH induced neuronal injury via regulating ER stress. Methods: The model of ICH was induced by injecting autologous blood (120 μl) into the rat striatum. Rats were divided into sham, normothermic (NT) and hypothermic (HT) groups. HT group were subjected to mild hypothermia (33 °C–35 °C) for 2 days starting from 6 h after ICH. Neurological deficits were evaluated. The ER stress related proteins (GRP78, CHOP and p-eIF2α) and the apoptosis associated indicators (cleaved caspase3, Bcl-2 and Bim) around hematoma were assessed by western blot, qRT-PCR (quantificational real-time polymerase chain reaction), immunofluorescence and TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick end labelling) assay. Results: Neurological deficits following ICH were reduced in HT group compared to NT group. Protein levels of GRP78, CHOP and p-eIF2α significantly increased after ICH in both NT and HT group compared to sham group, which was consistent with the trend of cleaved-caspase3 at protein level, and Bim, Bcl-2 at gene level. In comparison to NT group, GRP78, CHOP, p-eIF2α, cleaved caspase-3 and Bim all decreased, while Bcl-2 increased in HT group. Additionally, apoptotic cells detected by TUNEL staining significantly decreased in the HT group. Conclusion: Mild hypothermia could attenuate ICH caused neuron injury by decreasing ER response-induced neuron apoptosis.